A Secure Connection: Finding the Form of ASEAN Cyber Security Cooperation - Khanisa Krisman (JAS (Journal of ASEAN Studies), 2013)
Internet security is somehow being understated in ASEAN’s strategy facing 2015. ASEAN Connectivity as the blue print of ASEAN’s development strategy to strengthen the regional bond has not put proper attention in building security for guiding the connectivity plan among ASEAN member countries. This paper will discuss the future of cyber security cooperation particularly as ASEAN is planning to connect the region through ICT. This paper will try to analyse what kind of framework ASEAN will need on preparation to widen its security agenda to cyber world in the future to complete its preparation of being connected.